2019
DOI: 10.1534/g3.118.200941
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Mycoplasma dispar Provides Insights into Putative Virulence Factors and Phylogenetic Relationships

Abstract: Mycoplasma dispar is an important pathogen involved in bovine respiratory disease, which causes huge economic losses worldwide. Our knowledge regarding the genomics, pathogenic mechanisms, and genetics of M. dispar is rather limited. In this study, the complete genome of M. dispar GS01 strain was sequenced using PacBio SMRT technology and first genome-wide analyzed. M. dispar GS01 has a single circular chromosome of 1,065,810 bp en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
(64 reference statements)
0
12
0
Order By: Relevance
“…Interestingly, a study by Timsit et al, 2018 identified a distinct metacommunity, which was characterized by an over-representation of M. dispar (and other commensal bacteria such as Lactococcus lactis and Lactobacillus casei) in the lungs of healthy feedlot cattle. While M. dispar has been shown to have a number of virulence factors for bovine epithelial cells and can have immunosuppressive effects, it is associated with only milder respiratory infections and is likely not a causative agent for BP [48,50,51]. In general, Mycoplasma has a high affinity for binding to respiratory epithelial cells via adhesin proteins [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study by Timsit et al, 2018 identified a distinct metacommunity, which was characterized by an over-representation of M. dispar (and other commensal bacteria such as Lactococcus lactis and Lactobacillus casei) in the lungs of healthy feedlot cattle. While M. dispar has been shown to have a number of virulence factors for bovine epithelial cells and can have immunosuppressive effects, it is associated with only milder respiratory infections and is likely not a causative agent for BP [48,50,51]. In general, Mycoplasma has a high affinity for binding to respiratory epithelial cells via adhesin proteins [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…This bacterium has been previously isolated from the lungs of both healthy and pneumonic cattle [48][49][50]. immunosuppressive effects, it is associated with only milder respiratory infections and is likely not a causative agent for BP [48,50,51]. In general, Mycoplasma have a high affinity for binding to respiratory epithelial cells via adhesin proteins [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a study by Timsit et al, 2018 identified a distinct metacommunity which was characterized by an over-representation of M. dispar (and other commensal bacteria such as Lactococcus lactis and Lactobacillus casei) in the lungs of healthy feedlot cattle. While M. dispar has been shown to have a number of virulence factors for bovine epithelial cells and can have immunosuppressive effects, it is associated with only milder respiratory infections and is likely not a causative agent for BP [48,50,51]. In general, Mycoplasma have a high affinity for binding to respiratory epithelial cells via adhesin proteins [52,53].…”
Section: Discussionmentioning
confidence: 99%